Aspirasi Jarum Pentul yang Tertanam 10 Hari di Bronkus Kanan Seorang Remaja: [Aspiration of Implanted Pin in the Right Bronchus of a Teenager for More than a Week: A Case Report] - Isnu Pradjoko; Irmi Syafa’ah; Aries Subianto (Jurnal Respirasi, 2017)
Background: Foreign bodies can come from outside the body (exogenous) and in the body (endogenous). Foreign bodies can cause total obstruction resulting in atelectasis or partial obstruction with emphysema. Case: A 14-year-old girl with a cough with phlegm mixed with blood spots one day before admission. Patients swallowed needle 10 days ago while wearing jilbab while joking at school. Chest X-rays appear density of a metal with a long straight form of about 3.5 cm projected in the lower right hemitorac. Discussion: Performed Fiber Optic Bronchoscopy (FOB) with diagnostic and therapeutic indications for picking up foreign objects. In patients there is minimal bleeding post extraction pentul needle. Bleeding can be overcome by administering a cold sterile NaCl solution to the airway. Thoracotomy is not performed on the patient because the needle can be taken using FOB. Conclusion: Foreign bodies of the airways can be harmful. The needle extraction using FOB can rule out the need for thoracotomy in patients.